Induction of HOX Genes by Hepatitis C Virus Infection via Impairment of Histone H2A Monoubiquitination - Kasai, Hirotake; Mochizuki, Kazuki; Tanaka, Tomohisa; Yamashita, Atsuya; Matsuura, Yoshiharu; Moriishi, Kohji (Journal of virology, 2021)
Recently sustained virologic response can be achieved by direct-acting antiviral (DAA) therapy in most hepatitis C patients. Unfortunately, DAA therapy does not completely eliminate a risk of hepatocellular carcinoma (HCC). Hepatitis C virus (HCV) infection causes liver pathologies, including hepatocellular carcinoma (HCC). Homeobox (HOX) gene products regulate embryonic development and are associated with tumorigenesis, although the regulation of HOX genes by HCV infection has not been clarified in detail. We examined the effect of HCV infection on HOX gene expression. In this study, HCV infection induced more than half of the HOX genes and reduced the level of histone H2A monoubiquitination on lysine 119 (K119) (H2Aub), which represses HOX gene promoter activity. HCV infection also promoted proteasome-dependent degradation of RNF2, which is an E3 ligase mediating H2A monoubiquitination as a component of polycomb repressive complex 1. Since full-genomic replicon cells but not subgenomic replicon cells exhibited reduced RNF2 and H2Aub levels and induction of HOX genes, we focused on the core protein. Expression of the core protein reduced the amounts of RNF2 and H2Aub and induced HOX genes. Treatment with LY-411575, which can reduce HCV core protein expression via signal peptide peptidase (SPP) inhibition without affecting other viral proteins, dose-dependently restored the amounts of RNF2 and H2Aub in HCV-infected cells and impaired the induction of HOX genes and production of viral particles but not viral replication. The chromatin immunoprecipitation assay results also indicated infection- and proteasome-dependent reductions in H2Aub located in HOX gene promoters. These results suggest that HCV infection or core protein induces HOX genes by impairing histone H2A monoubiquitination via a reduction in the RNF2 level. IMPORTANCE Recently sustained virologic response can be achieved by direct-acting antiviral (DAA) therapy in most hepatitis C patients. Unfortunately, DAA therapy does not completely eliminate a risk of hepatocellular carcinoma (HCC). Several epigenetic factors, including histone modifications, are well known to contribute to hepatitis C virus (HCV)-associated HCC. However, the regulation of histone modifications by HCV infection has not been clarified in detail. In this study, our data suggest that HCV infection or HCV core protein expression impairs monoubiquitination of histone H2A K119 in the homeobox (HOX) gene promoter via destabilization of RNF2 and then induces HOX genes. Several lines of evidence suggest that the expression of several HOX genes is dysregulated in certain types of tumors. These findings reveal a novel mechanism of HCV-related histone modification and may provide information about new targets for diagnosis and prevention of HCC occurrence.